ESP LEARNING STYLE PREFERENCES OF VOCATIONAL STUDENTS AND UNIVERSITY STUDENTS: A COMPARATIVE REVIEW AND IMPLICATIONS FOR ESP TEACHERS - Yao Liuchi; Nadhratunnaim Abas; Norwati Roslim, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Research in English for Specific Purposes (ESP) has been conducted extensively throughout the past few decades. The dichotomy between vocational and general tertiary education in ESP classrooms has attracted particular attention. Despite attending ESP classes, students encounter embarrassing situations when they cannot use English effectively in real-life workplace conditions, which is problematic regarding ESP teacher building and ambiguous learning style identification. This article aims to extend a systematic literature review on the preferences of students from vocational institutes and universities regarding ESP learning style and to determine the implications for ESP teachers. The search was conducted using a variety of databases and journals for the period from 2019 to 2023. Two groups of students showed significant differences. Vocational students are more motivated kinesthetic, and prefer hands-on experience than university students. Teacher-modelling, accommodating, and converging learning styles are preferred by university students. The result of this review is expected to encourage ESP teachers to implement broad teaching strategies and prepare diverse lesson plans that will be effective for their students.